Reception of the Conciliar Decree «Optatam Totius» in the General Conferences of the Latin American Episcopate - Costadoat, Jorge-Eduardo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2022)
This publication addresses the acceptance from the latest general Latinamerican and Caribbean episcopal conferences to the Optatam Totius. This document refers to the formation of the clergy. It gives particular importance to Medellín’s conference as it has updated the conciliar teaching in the continent and dedicated a full chapter to the topic. Notwithstanding its limits, Medellín claimed the need for supporting seminarians in discerning the «signs of the times». However, subsequent conferences such as Puebla, Santo Domingo and Aparecida progressively moved away from the innovation proposed by Medellín and the Second Vatican Council’s decree. Therefore, we should not think that the Latinamerican and Caribbean Churches have accepted Optatam Totius creatively as it usually appears in the Latinamerican discussions regarding the Second Vatican Council.
Keywords: Optatam totius; formation of the clergy; Medellín; reception of Vatican II